ANALISIS DAMPAK SERTIFIKAT PENDIDIK DALAM PEMENUHAN STANDAR PTK (PENDIDIK DAN TENAGA KEPENDIDIKAN) (STUDI DI SD NEGERI GEDANGANAK 02) - Ayu Rosydina; Haniatul Masúdah; Sudjono, Sudjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
An educator certificate is important as a professional standard for teachers to guarantee the quality and standards of educators and education personnel. The standard for educators and educational personnel is one of the national educational standards that educators and educational personnel need to have. In this case, fulfilling academic and non-academic qualifications is very necessary in fulfilling PTK standards which can be seen from the ownership of each teacher's teaching certificate. SD Negeri Gedanganak 02 is located in East Ungaran District, Semarang Regency which has 9 teaching and education personnel. This research aims to examine the impact of teacher certification on the implementation of standards for educators and education personnel at SD Negeri Gedanganak 02. The method used in this research is a qualitative method with a descriptive research type. Data collection methods through interviews, observation and documentation. The research results show that the principal of SD Negeri Gedanganak 02 has met general qualifications and special qualifications. For teaching staff, there are six teachers who do not yet have an educator certificate. In non-academic qualifications, all educators and education staff at SD Negeri Gedanganak 02 have fulfilled four main competencies.